1990
DOI: 10.1002/pssa.2211190109
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of the Ferroelectric Phase Transition in the Mössbauer Parameters of the System (SnxPb1−x)2P2S6

Abstract: The system of ferroelectric solid solutions (SnxPb1−x)2P2S6 with x = 0.95; 0.9; 0.8; 0.6; 0.5; 0.4 is studied by means of the Mössbauer effect on 119Sn nuclei at room temperature. In the region of the ferroelectric phase transition kinks in the concentration dependencies of the line width, Mössbauer spectrum area, absolute Mössbauer effect probability, effective Debye temperature, and mean‐square displacements of tin atoms from equilibrium have been observed. The isomer shift increases linearly with the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Observed location of TCPs at same temperature level ("temperature waterline") for different mechanical or chemical impacts (at compression of Sn 2 P 2 S 6 and at S by Se or Sn by Pb substitution) (figure 12) could be explained by the following way. At sulfur by selenium replacement, the intercell interactions become weaker in result of more covalent chemical bonds [23,24], but the Sn 2+ cations stereoactivity and shape of the local potential obviously remain almost unchanged. These factors, mostly the intercell interactions weakening, determine the second order PT temperature lowering until reaching the TCP.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observed location of TCPs at same temperature level ("temperature waterline") for different mechanical or chemical impacts (at compression of Sn 2 P 2 S 6 and at S by Se or Sn by Pb substitution) (figure 12) could be explained by the following way. At sulfur by selenium replacement, the intercell interactions become weaker in result of more covalent chemical bonds [23,24], but the Sn 2+ cations stereoactivity and shape of the local potential obviously remain almost unchanged. These factors, mostly the intercell interactions weakening, determine the second order PT temperature lowering until reaching the TCP.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…13) can be explained in the following way. On substitution of sulfur by selenium, intercell interaction becomes weaker as a result of the stronger covalence of the chemical bonds [24,25], but the stereoactivity of the Sn 2+ cations and the form of the local potential obviously remain almost unchanged. These factors, mostly the intercell interaction weakening, determine the secondorder PT temperature decrease until the TCP is reached.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously Mössbauer spectroscopy was used in the Sn 2 P 2 S 6 crystal investigation [11][12][13]. It has been found that ionicity of Sn-S bonds is high enough -around 70%.…”
Section: +mentioning
confidence: 99%
“…The pseudobrookite, Fe 2 TiO 5 phase has exhibited diverse characteristics like the gas sensing ability, magnetic properties and photocatalytic properties which have been exploited previously for various applications [133][134][135][136][137][138]. Very recently, a novel yellow pigment, Fe 2 TiO 5 decorated mica composites was evaluated for its near infrared reflectance ability which makes it a good candidate as solar reflective coating [139].…”
Section: Fe 2 Tio 5 As a Photoanode Materialsmentioning
confidence: 99%